ANALYSIS OF KEY PERFORMANCE INDICATORS AND QUALITY OBJECTIVES OF A TERTIARY CARDIAC CENTER - Maqsood, Muhammad Bilal; Zaidi, Sabeen Khurshid; Naqvi, Shahab; Aziz, Sohail; Baig, Farrakh (Pakistan Armed Forces Medical Journal, 2015)
Objective: To analyze the contribution of departments of a tertiary cardiac center before and after the training intervention and to assess the impact of key performance indicators and quality objectives on the quality improvement drive. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at AFIC/NIHD Rawalpindi from Jan 2013 to Dec 2014. Methods: Data was collected from twelve clinical and support departments of AFIC&NIHD, Pakistan after conducting series of knowledge/training sessions on formation of Quality objectives and Key performance indicators. Parameters for the years 2013 & 2014 were entered in Microsoft Excel 2010 and data was analyzed mthrough descriptive statistics. Results: The results revealed that nine out of nineteen (47%), selected departments responded with KPIs after one month whereas eight depts. (42%) made quality objectives and twelve depts. (63%) presented quality metrics for the year 2014. This practice contributed effectively towards quality improvement drive as last year there were no KPIs (0%), four quality objectives (21%) and only eight (42%) depts. provided quality metrics for the year 2013. Conclusion: The study concluded that involvement of departments in quality activities and collection of useful quality data contributes towards quality improvement drive. KPIs help in benchmarking processes and improving the clinical and administrative performance. Quality objectives aligned with KPIs provide thrust to improve quality over a longer period. The KPIs, quality objective and quality metrics are important ingredients in the quality improvement drive which lead to successful implementation of quality management system.